Ginger Compress and Warm Lemongrass Compress Therapy for Pain Reduction among Elderly with Rheumatoid Arthritis: A Case Study - Wasis Eko Kurniawan; Jepri Riranto (Alta Dharma Publisher, 2022)
Background: Rheumatoid Arthritis (RA) is a chronic autoimmune inflammatory disorder in which a person's immune system can be compromised and lowered, which destroys the joints and lining of the synovial membrane, especially in the hands, feet, and knees. Objective: The study aimed to examine the effect of ginger compresses, and warm lemongrass compresses on pain reduction among elderly with rheumatoid arthritis. Method: A case study was conducted from January 25, 2022, to January 27, 2022, at the